2018
DOI: 10.1111/vsu.12937
|View full text |Cite
|
Sign up to set email alerts
|

Arthroscopic placement of a toggle rod to correct coxofemoral luxation in a dog

Abstract: Minimally invasive, arthroscopic guided toggle rod stabilization may be an alternative to the currently accepted open approach when addressing coxofemoral luxations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(16 citation statements)
references
References 22 publications
1
15
0
Order By: Relevance
“…1,12 However, previous studies in which coxofemoral luxation has been examined have included cases with mild to moderate hip dysplasia. 2,5,6,8,9 Researchers in a previous retrospective study in which a toggle rod was used found that, of 10 hips with mild hip dysplasia, only one hip reluxated. 5 Other researchers have observed that dogs with hip dysplasia did not experience reluxation.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,12 However, previous studies in which coxofemoral luxation has been examined have included cases with mild to moderate hip dysplasia. 2,5,6,8,9 Researchers in a previous retrospective study in which a toggle rod was used found that, of 10 hips with mild hip dysplasia, only one hip reluxated. 5 Other researchers have observed that dogs with hip dysplasia did not experience reluxation.…”
Section: Discussionmentioning
confidence: 99%
“…Hip pathology has historically been stated as a contraindication for performing a toggle rod stabilization 1,12 . However, previous studies in which coxofemoral luxation has been examined have included cases with mild to moderate hip dysplasia 2,5,6,8,9 . Researchers in a previous retrospective study in which a toggle rod was used found that, of 10 hips with mild hip dysplasia, only one hip reluxated 5 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Rocheleau also described the use of a custom C-guide for arthroscopic application. 15 The standard C-guide described by Kieves and colleagues does not have a shallow enough reach to allow for placement in the fovea capitis without near complete luxation of the hip, making it more difficult to use in an arthroscopically guided setting. 4 In four of eight cases, the femoral bone tunnel was found to enter the intertrochanteric fossa; however, the aperture of the drill tunnel exit was completely located in the fovea capitis in three out of the four cases that had intertrochanteric fossa penetration.…”
Section: Discussionmentioning
confidence: 99%
“…Rocheleau also described the use of a custom C-guide for arthroscopic application. 15 The standard C-guide described by Kieves and colleagues does not have a shallow enough reach to allow for placement in the fovea capitis without near complete luxation of the hip, making it more difficult to use in an arthroscopically guided setting. 4…”
Section: Discussionmentioning
confidence: 99%